Pengaruh Model Pembelajaran Self Organized Learning Environment (SOLE) Berbantuan E-LKPD Terhadap Hasil Belajar Peserta Didik Materi Sistem Pencernaan - Arfani, Arfani; Syamsul, Syamsul; Maulana, Andi (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
The research objectives are: to determine the learning outcomes of students who are taught with the use of SOLE learning model assisted by E-LKPD on the learning outcomes of students of digestive system material at SMPN 06 Mamuju, to determine the learning outcomes of students who are taught without the use of SOLE learning model assisted by E-LKPD on the learning outcomes of students of digestive system material at SMPN 06 Mamuju, to determine the effect of SOLE learning model assisted by E-LKPD on the learning outcomes of students of digestive system material at SMPN 06 Mamuju. Type of research Quasi Experiment with Non-Equivalent Control Group Design. Sample selection using purposive sampling in class VIII A as many as 20 people and class VIII B 20 people. The instruments used were learning outcome tests and observation sheets that had been validated. The results of the study were obtained by descriptive and inferential analysis. The learning outcomes of students in the experimental class with an average value of 82.25 were higher than the control class with an average value of 67.00. Hypothesis testing of learning outcomes shows titung 0.000 <0.05 so it is concluded that there is a significant difference between the learning outcomes of students taught using the SOLE learning model assisted by E-LKPD and students taught without using the SOLE learning model assisted by E-LKPD.